The Prague School Theory of Drama & Theatre and SFL - Quammie-Wallen, Patrice (Technium Social Sciences Journal, 2020)
The Prague Linguistic Circle’s theories of drama and theatre were ground-breaking in the early 20th century. While the many and varied writings of its scholars are only recently gaining global recognition the application of the many semiotic principles as it applies to the stage remain to be fully utilised. Literary analyses over the modern decades have comparatively ignored the play text for stylistic treatment, due significantly to the fact that a suitable framework that can manage the ‘combinatory quality of theatre’ remains at large. Systemic functional linguistics (SFL), a developed, language-based semiotic framework whose foundations share Prague School principles of structure and function, has been suggested to be capable of managing that combinatory quality. This paper, agreeing with that position, compares Prague School principles with that of SFL to advance the further position that combined use of SFL and Prague theatre theories can potentially construct that elusive primary dynamic connecting the page and the stage, as well as facilitate mutual development of both frameworks.